Factors associated with the failure of the neuroprotector therapies in the clinical phase of animal models with cerebral ischemia - Javier Enrique Almenares Rosales; Amanda Moya Gómez; Lena Pérez Font (Centro Provincial de Información de Ciencias Médicas, 2021)
The strokes have been considered, worldwide, as the third cause of death and the first cause of disability. To diminish the incidence of ischemia cases or cerebral hemorrhage, as well as their consequences, one should have the knowledge on this clinical entities, the associated risk factors and preventive and therapeutic alternatives as neuroprotector strategies. Many of the medical interventions carried out so far in animal models have been unsatisfactory in the clinical phase. Reason why, a review of the most recent publications was carried out, where the most used experimental models for the cerebral ischemia in the evaluations of the neuroprotector therapies are approached, and it was concluded that if protocols used in the preclinic phase are analyzed, the investigations could be optimize  to achieve more relevant results in this field.